PENYERAPAN LOGAM BERAT SECARA BIOKIMIAWI OLEH BAKTERI GRAM POSITIF DAN GRAM NEGATIF: A MINI RIVIEW - Mahrus, Muhammad Haissul; Kartika, Rudi; Fahmi, Miraz’ul; Dimas P, Riansyah; Rahman, Fathur; Aswat, Raihan; Rizkirullah, M. Adhitya (PROSIDING SEMINAR KIMIA, 2024)
Dyes are one source of heavy metal waste originating from the textile industry, this is caused by the manufacture of dyes that use heavy metals as catalysts. Heavy metals are very dangerous because they cannot be broken down or degraded. Wastewater produced from the textile industry can contain dangerous metals, namely chromium (Cr), copper (Cu) and lead (Pb), where if these metals enter water bodies they can damage the food chain. Therefore, an alternative method is used that can reduce this waste, namely the biosorption method using microorganisms in the form of bacteria. This research uses gram positive bacteria in the form of Streptococcus mutans bacteria which will be exposed to chromium (VI) metal and gram negative bacteria in the form of Flavobacterium sp bacteria which will be exposed to lead (Pb) metal and Pseudomonas sp bacteria which will be exposed to chromium (VI) metal, lead. (Pb), and copper (Cu). The aim of this research was to determine the absorption ability of negative and gram-positive salt bacteria on these heavy metals. Literature results show that Streptococcus mutans bacteria are able to absorb chromium (VI) metal with a maximum of 90.80% with a concentration of 5 ppm on the 5th day. Flavobacterium sp bacteria are able to absorb lead metal (Pb) with a maximum of 96% with a concentration of 2 ppm on the 18th day, while Pseudomonas sp bacteria are able to absorb chromium (VI) metal with a maximum of up to 96.192% with a concentration of 5 ppm on the second day. -14, lead(Pb) metal can be absorbed to a maximum of 36.874% with a concentration of 4 ppm on the 16th day and Cu(II) metal can be absorbed to a maximum of 84.447% with a concentration of 3 ppm on the 16th day. Keywords: Biosorption, Bacteria, Metal